2017
DOI: 10.1161/atvbaha.117.308992
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Factor With G Patch and FHA Domains 1 Is a Novel Regulator of Vascular Injury

Abstract: Objective— Phenotypic modulation of vascular smooth muscle cells represents a hallmark event in vascular injury. The underlying mechanism is not completely sorted out. We investigated the involvement of angiogenic factor with G patch and FHA domains 1 (Aggf1) in vascular injury focusing on the transcriptional regulation of vascular smooth muscle cell signature genes. Approach and Results— We report here that Aggf1 expression was downregulated in several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Histone deacetylase enzymes regulate diverse biological function, including gene expression, rendering them potential targets for intervention in a number of diseases (Moreno-Yruela et al, 2018). Among the human zinc-dependent histone deacetylase enzymes, the most recently discovered member, HDAC11, has been shown to play a role in CVDs through promoting apoptosis, oxidative stress and inflammation (Zhou et al, 2017;Fan et al, 2018). A study showed that peritoneal injection of a small-molecule HDAC11 inhibitor significantly attenuated the formation of neointima after carotid artery ligation in Sprague-Dawley rats (Fan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone deacetylase enzymes regulate diverse biological function, including gene expression, rendering them potential targets for intervention in a number of diseases (Moreno-Yruela et al, 2018). Among the human zinc-dependent histone deacetylase enzymes, the most recently discovered member, HDAC11, has been shown to play a role in CVDs through promoting apoptosis, oxidative stress and inflammation (Zhou et al, 2017;Fan et al, 2018). A study showed that peritoneal injection of a small-molecule HDAC11 inhibitor significantly attenuated the formation of neointima after carotid artery ligation in Sprague-Dawley rats (Fan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that HDAC11 compromised the vascular endothelial barrier function by suppressing the expression of Ve-cadherin (Zhang and Ge, 2017). Besides, it has been reported that treatment of the HDAC11 inhibitor attenuated vascular injury in mice (Zhou et al, 2017). These studies suggested that HDAC11 was involved in CVDs.…”
Section: Introductionmentioning
confidence: 94%
“…However, this result was different from the previous findings in mice model of carotid artery injury. After carotid artery injury in mice, Aggf1 expression was decreased in the carotid arteries [ 31 , 32 ]. We supposed that such discrepancy may be due to the difference in animal models and tissue types.…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of this article, Zhou et al 65 reported that overexpression of AGGF1 using adenoviruses inhibited neointimal formation induced by carotid artery ligation. However, there are several major differences between our study and that by Zhou et al First, we presented the data on neointimal formation from AGGF1 +/À KO mice, but the Zhou et al study did not have such data.…”
Section: Discussionmentioning
confidence: 99%